The pool of pedogenic carbon in the soils of different types and durations of use as croplands in the forest-steppe of the Central Russian Upland - Khokhlova, O. S.; Chendev, Yu. G.; Myakshina, T. N.; Shishkov, V. A. (Eurasian soil science, 2013)
Based on studying five agrochronoseries, including recent forest (dark) gray soils and soils plowed for 100, 150, and 200–240 and more years in the forest-steppe zone of the Central Russian Upland, the dynamics of the pedogenic carbon pool, including the C org and C carb , are considered. In the 2-m-thick layer of the agrogenic soils studied, the pedogenic carbon pool was shown to increase by 15–30% (up to 50%) mainly due to the changes in the C carb content. The insignificant (by ∼10%) growth of the C org content was found in the soils that were plowed for more than 200–250 years. As the hydrothermal regime changed when passing from the forest to croplands, the C carb reserves increased due to the ascending of carbonates from the parent rock through the capillary pores, probably, in colloid solution-suspensions. This process proceeded without exchange with the soil CO 2 , since the 14 C age and the content of the newly formed carbonates became higher. These carbonates may be called pedogenic-lithogenic agrocarbonates, since they appear in soils as a result of the (agro-) pedogenesis. In this case, their additional source is the lithogenic carbonates, which bring in the “old” carbon. The process of carbonates ascending could be referred to the rapid soil-forming ones with their implementation time being close to ≤50 years.